High pressure and temperature spinning capillary cell for in-situ synchrotron X-ray powder diffraction - Fraga, Edmundo; Yáñez, Armando; Zea-Garcia, Jesus D.; Gómez-de-la-Torre, María de los Ángeles; Cuesta-García, Ana María; Valcárcel-Fernández, Ricardo; Farré-París, Francesc; Malfois, Marc; García-Aranda, Miguel Ángel (My University, 2019)
In situ research of materials under moderate pressures (hundreds of bar) is essential in many scientific fields. These range from gas sorption to chemical and biological processes. One industrially important discipline is the hydration of oil well cements. Existing capillary cells in this pressure range are static as they are easy to design and operate. This is convenient for the study of single-phase materials; however, powder diffraction quantitative analyses for multiphase systems cannot be performed accurately as a good powder average cannot be attained. Here, the design, construction and commissioning of a cost-effective spinning capillary cell for in situ powder X-ray diffraction is reported, for pressures currently up to 200 bar. The design addresses the importance of reducing the stress on the capillary by mechanically synchronizing the applied rotation power and alignment on both sides of the capillary while allowing the displacement of the supports needed to accommodate different capillaries sizes and to insert the sample within the tube. This cell can be utilized for multiple purposes allowing the introduction of gas or liquid from both ends of the capillary. The commissioning is reported for the hydration of a commercial oil well cement at 150 bar and 150°C. The quality of the resulting powder diffraction data has allowed in situ Rietveld quantitative phase analyses for a hydrating cement containing seven crystalline phases.
Keywords: Materiales a altas presiones; Resistencia de materiales; Pozos petrolíferos - Materiales; Cemento; High-pressure equipment; Oil well cement; Cement hydration; Rietveld quantitative phase analysis